Rotational Distraction for the Treatment of Severe Mandibular Retrognathia - Ito, Osamu (Plast Reconstr Surg Glob Open, 2015)
BACKGROUNDS: The main problem with intraoral distraction of the mandible is the inability to achieve the three-dimensional mandibular correction as planned preoperatively. We developed a technique that allows spontaneous changes in the direction of mandibular elongation using an intraoral distractor. METHODS: After mandibular osteotomy, the distractor is fixed to the distal segment of the mandible using a single bicortical screw, allowing anterior-posterior, vertical and limited lateromedial changes in the vector of distraction. Mandibular lengthening is performed while keeping the maxilla and mandible in class I occlusion with intermaxillary fixation. RESULTS: As the distraction device is activated allowing mandibular elongation, the proximal segment, guided by the surrounding soft tissues, moves and rotates posterosuperiorly. Mandibular lengthening is continued until the condylar head reaches an adequate position in the mandibular fossa as confirmed clinically and radiographically. CONCLUSION: Thirty-three patients with mandibular retrognathia received this treatment and good results were obtained.